Response to Tenofovir Among Lamivudine-experienced Hepatitis B and HIV-coinfected Adolescents - Linda Aurpibul (2018)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. We determined hepatitis B virus (HBV) suppression rates among 18 lamivudine (3TC)-experienced HBV-human immunodeficiency virus-coinfected adolescents after treatment with tenofovir disoproxil fumurate (TDF). At TDF initiation, their median age was 17.6 years, and duration of 3TC exposure was 7.3 years. Eleven patients (61%) achieved HBV DNA <60 IU/mL after 48 weeks on TDF and 3TC which was similar to adult studies, although hepatitis B surface antigen loss or hepatitis B envelope antigen seroconversion did not occur.